Atypical nontraumatic chylothorax in a monoclonal IgM elevated nodal marginal zone lymphoma: A case report and review of the literature - Wang, Lingling; Huang, Qian; Tang, Jiao; Feng, Jun; Huang, Yongfen; Dong, Jianming; Cheng, Yuexin; Xu, Hao; Miao, Yuqing (Frontiers in Immunology, 2022)
Nodal Marginal Zone Lymphoma(NMZL) is an indolent lymphoma with a very low clinical incidence and is sometimes difficult to differentiate diagnostically from Lymphoplasmacytic lymphoma /Waldenstrom macroglobulinemia (LPL/WM). NMZL with elevated monoclonal immunoglobulin M (IgM) is even rarer. Nontraumatic chylothorax can be seen in aggressive lymphoma, which often happens with chest tightness and dyspnea as the primary clinical manifestation. We reported the first case of monoclonal IgM elevated NMZL complicated by atypical nontraumatic chylothorax. A 64-year-old male patient was first admitted to the Department of Respiratory Medicine with symptoms of chest tightness and shortness of breath. He was given several times thoracentesis to drain pleural effusion to improve pulmonary compression symptoms. The patient had a combination of elevated monoclonal IgM and atypical lymph node biopsy pathology. After two times lymph node biopsies and genetic testing, the patient was finally diagnosed with NMZL. Within a short time, he was admitted to the Department of Hematology due to the reappearance of massive pleural effusion, which indicated chylothorax. The patient repeatedly presented with left-sided pleural effusion, and the color went from red to yellow, and finally white. Only about half of the chylothorax cases present with typical clinical manifestations. We report this case intending to draw the attention of clinicians to hematologic malignancies with atypical nontraumatic chylothorax.